Effects of dietary chromium picolinate supplementation on serum glucose, cholesterol and minerals of rainbow trout (Oncorhynchus mykiss) - Kucukbay, F. Z.; Yazlak, H.; Sahin, N.; Cakmak, M. N. (Springer, 2006)
The effect of chromium (chromium picolinate, CrPic) supplementation at various levels (0, 400, 800 or 1600 mu g Cr/kg diet) on serum concentrations of glucose and cholesterol and on serum and liver concentrations of Cr, Zn, Cu and Fe of rainbow trout (Oncorhynchus mykiss) was evaluated. One-year-old rainbow trout (n=120) were randomly assigned to four treatment groups, each with two replicates of 15 fish. The fish were fed either a control diet or the control diet supplemented with either 400, 800 or 1600 mu g Cr/kg diet. Serum glucose and cholesterol concentrations decreased (p=0.001) with higher dietary chromium supplementation. Increasing dietary chromium supplementation linearly increased serum chromium and zinc concentrations (p=0.001). Serum copper and iron concentrations did not change (p > 0.10) as dietary chromium supplementation increased. Liver chromium and zinc concentrations linearly increased (p=0.001). Also, liver Cu and Fe concentrations did not change (p > 0.10) as dietary chromium supplementation increased. The results of present study conclude that supplemental chromium to the diet of rainbow trout influences serum and liver Cr and Zn concentrations, thus most probably functions of the organs as well as the welfare of raibow trout.
Keywords: cholesterol; chromium; glucose; minerals; rainbow trout